Genomic structure and functional trait variation are decoupled across the Atacama–Patagonia arid gradient in the Chilean wineberry - Cordero, Sebastián; Carvallo, Gastón O.; Coronado, Tania; Rosas, Marcelo R.; Romeiro-Brito, Monique; Majure, Lucas C.; Saldaña, Alfredo; Villalobos-Barrantes, Heidy M.; Guerrero, Pablo C. (Frontiers in Plant Science, 2026)
Local adaptation to aridity is often expected to promote genomic divergence by favoring the integration of drought-tolerance traits. Under this framework, functional trait variation should align with genetic structure; however, empirical evidence for such coupling remains limited, particularly when experimental validation is lacking. We tested this prediction in Aristotelia chilensis, a phenotypically variable tree spanning a 1,500-km precipitation gradient (<100 to >1,000 mm year−1). We combined nextRAD population genomics, trait–environment modeling, and a common garden drought experiment to assess how climatic and edaphic factors shape genomic structure, drought-related functional traits, reproductive traits, and antioxidant profiles. We identified four genetically distinct clusters that correspond to major biomes across the species’ range—from the Atacama Desert to northern Patagonia—reflecting strong spatial genetic structuring. In contrast, functional traits were largely decoupled from genomic structure and responded independently to environmental variables. Critical photo-inactivation water content (SWC-PhI) showed no credible environmental associations but exhibited significant hierarchical variation among populations and clusters. Specific leaf area (SLA) was strongly influenced by edaphic conditions, decreasing with soil sand content and increasing with soil water-retention capacity, with most variation attributable to population-level differences. Root–shoot biomass ratio also varied hierarchically but was unrelated to climatic or soil predictors. Survival under experimental drought was uniformly low (1.7%) and did not differ among populations or clusters, indicating conserved physiological tolerance across the range. Together, these findings reveal that adaptation to aridity in A. chilensis arises from trait-specific, uncoupled responses rather than from an integrated drought-resistance syndrome. The pronounced genomic structure appears more consistent with historical biogeographic processes than with contemporary drought adaptation. These insights underscore the importance of selecting genotypes based on empirical trait performance under water stress—rather than geographic origin—to support climate-resilient fruit production and guide restoration strategies involving A. chilensis.